Can Islands of Effectiveness Thrive in Difficult Governance Settings? The Political Economy of Local-level Collaborative Governance - Levy, Brian (2012)
Many low-income countries contend with a governance syndrome characterized by a difficult combination of seeming openness, weak institutions, and strong inter-elite contestation for power and resources. In such countries, neither broad-based policy nor public management reforms are likely to be feasible. But are broad-based approaches necessary? Theory and evidence suggest that in such settings progress could be driven by "islands of effectiveness" -- narrowly-focused initiatives that combine high-quality institutional arrangements at the micro-level, plus supportive, narrowly-targeted policy reforms. This paper explores whether and how local-level collaborative governance can provide a platform for these islands of effectiveness. Drawing on the analytical framework developed by the Nobel-prize winning social scientist Elinor Ostrom, the paper reviews the underpinnings of successful collaborative governance. It introduces a simple model for exploring the interactions between collaborative governance and political economy. The model highlights the conditions under which coordination is capable of countering threats from predators seeking to capture the returns from collaborative governance for themselves. The relative strength in the broader environment of two opposing networks emerges as key -- "threat networks" to which predators have access, and countervailing "trumping networks" on which protagonists of effective collaborative governance can draw. The paper illustrates the potential practical relevance of the approach with three heuristic examples: the governance of schools, fisheries, and road construction and maintenance. It concludes by laying out an agenda for further empirical research, and suggesting what might be the implications of the approach for future operational practice.